Exploring Halal Certification Literacy Measurement for Micro Small Enterprises (MSEs) - Fathoni, Muhammad Anwar; Faizi, Faizi; Suprima, Suprima; Wiryanto, Fadhli Suko; Suryani, Suryani (Universitas Pendidikan Indonesia, 2024)
Purpose – The study aims to explores the development of a Halal Certification Literacy Index (HCI) as a novel approach to address challenges faced by Micro and Small Enterprises (MSEs) in obtaining halal certification in Indonesia.Methodology – Employing a qualitative methodology, this research utilizes a comprehensive literature review to construct a conceptual framework for measuring halal certification literacy. The study investigates the current landscape of halal certification, focusing on regulatory frameworks, certification procedures, and the role of government bodies.Findings – The research identifies key challenges such as lack of awareness, financial constraints, and bureaucratic complexities hindering MSEs in obtaining halal certification. The proposed HCI assesses components like knowledge and awareness, procedural readiness, financial capability, human resource competency, and technological adoption.Practical Implications – By introducing the HCI, this study provides a practical tool for policymakers, businesses, and consumers to navigate and enhance the halal certification process. The HCI can facilitate targeted interventions to improve literacy, streamline certification procedures, and support MSEs in meeting halal compliance, ultimately boosting their competitiveness and market access.Originality/Value – This study introduces a novel Halal Certification Literacy Index, which offers a structured approach to measuring and improving halal literacy. The HCI represents an innovative contribution to the field, potentially setting a benchmark for similar indices in other regions and sectors within the halal industry.